2023
DOI: 10.1111/csp2.12918
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and workplace risk inequalities among conservation professionals

Abstract: Workplaces can be sources of both stress and support, affecting employees' mental health and productivity. Yet, little research has investigated variability in workplace risk factors for poor mental health in conservation. We aimed to explore how patterns of psychological distress—a state of emotional disturbance—and associated workplace risk factors vary between conservation job roles. Working with three case study organizations in India, South Africa, and Cambodia, we surveyed 280 field‐based, office‐based, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 75 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…One metaanalysis of 8 cohort studies and 84,963 employees showed that workers exposed to higher ERI had a significantly greater subsequent risk of poor mental health (Rugulies et al, 2017). Furthermore, the positive association between ERI and distress was observed in a companion study among 280 field-based, office-based, and research staff working in 3 conservation organizations in Cambodia, India, and South Africa (Pienkowski et al, 2023). As such, the observed associations between the ERI score (and many of its constituent items) and psychological distress may be widely relevant for the conservation sector.…”
Section: Workplace Mental Health In Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…One metaanalysis of 8 cohort studies and 84,963 employees showed that workers exposed to higher ERI had a significantly greater subsequent risk of poor mental health (Rugulies et al, 2017). Furthermore, the positive association between ERI and distress was observed in a companion study among 280 field-based, office-based, and research staff working in 3 conservation organizations in Cambodia, India, and South Africa (Pienkowski et al, 2023). As such, the observed associations between the ERI score (and many of its constituent items) and psychological distress may be widely relevant for the conservation sector.…”
Section: Workplace Mental Health In Conservationmentioning
confidence: 99%
“…For example, multiple recent studies examine workplace stressors (e.g., isolation from family, poor health and safety, and inadequate compensation) experienced by conservation rangers (e.g., Anagnostou et al, 2022;Belhekar et al, 2020;Gao & Li, 2021;Moreto, 2016;Singh et al, 2020). Pienkowski et al (2023) surveyed 280 conservationists in 3 organizations in 3 countries and found that field-based employees were more likely to report imbalances between workplace efforts and rewards, in turn associated with higher psychological distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation